Smart and Resilient Infrastructure For Emerging Economies: Perspectives on Building Better Proceedings of the 9th International Conference on Development and Investment In infrastructure (DII-2023, 19-21 July 2023, Zambia) - MUSONDA, INNOCENT; Mwanaumo, Erastus; Onososen, Adetayo; Moyo, Thembani (Taylor & Francis, 2024)
Smart and Resilient Infrastructure For Emerging Economies: Perspectives on Building Better is about pressing and multidimensional challenges faced in constructing resilient, sustainable, and smart infrastructure in developing countries. The 32 case studies, literature reviews, comparative analyses and systematic reviews, cover a wide range of topics, including: sustainable and resilient infrastructure development smart cities digital innovation in construction infrastructure investment construction ergonomics socio-environmental sustainability gender equity, and climate change responses The contributions present innovative solutions, impactful insights, and substantive contributions to the discourse on sustainable infrastructure development, and illuminate the interplay between infrastructure development, social justice, environmental sustainability, and technological advancement. Smart and Resilient Infrastructure For Emerging Economies: Perspectives on Building Better is essential reading for academics, researchers, practitioners, policymakers, and students involved in the built environment, infrastructure delivery, investment in infrastructure, civil engineering, architecture, urban planning, environmental science, and other related disciplines.